Breaking the nurse's no-dating rule - Lynn, Janice (Harlequin medical romance., 2024)
Nurse Julia has a life plan and dreamy Dr. Boone Richards isn't in it. Adamant that history won't repeat itself, she's set herself a list of rules. Number one is absolutely no dating! But the rule book's soon thrown out the window by their overwhelming attraction... Yet, discovering her and Boone's pasts are tainted with the same brush could bring them even closer-- if Julia can open her heart and let him in...